PROBLEM TERHADAP PERKEMBANGAN KECERDASAN DAN SOLUSINYA (berdasarkan Agama Islam) (Pendidikan Kecerdasan Spiritual dalam Al-Qur’an Surat Luqman) - Aryani, Wiwik Dyah; Salsabilah, Iis; Mubarok, Ece; Saripudin, Saripudin; Dudung, Dudung; Nurdin, Ali (Penerbit Widina, Widina Media Utama, 2022)
A person who is intelligent, his speech will be structured and have value. When he speaks, what comes out are ideas, thoughts, solutions, wisdom, knowledge and dhikr, so that his speech is always beneficial. Intelligence is one of the great gifts from Allah to humans and makes it one of the advantages of humans compared to other creatures. Because with intelligence, humans can continuously maintain and improve their quality of life which is increasingly complex, through the process of thinking and learning continuously. Spiritual intelligence is the ability to give religious meaning to every behavior and activity, through steps and thoughts that are fitrah, towards a whole human being, and has a tauhidi mindset, and is principled